The impact of state earned income tax credit increases on material and medical hardship. Issue 3 (19th June 2021) - Kondratjeva, Olga; Roll, Stephen P.; Despard, Mathieu; Grinstein‐Weiss, Michal
Abstract: The federal Earned Income Tax Credit (EITC) provides substantial financial assistance to low‐ and moderate‐income workers and has been shown to reduce poverty and encourage employment. Many US states have also implemented their own EITCs to supplement the federal tax credits. Leveraging unique administrative and survey data and employing a difference‐in‐differences approach, this study investigates how changes in state EITC benefits between 2012 and 2016 impacted the levels of material and medical hardships in states that expanded or enacted state credits. We find that small changes in state EITC levels can alleviate medical hardship, but not most other types of hardship, especially when states experience a greater benefit increase or implement new state EITCs. Our research points to the limitations of using relatively modest tax credits to offset many of the economic challenges faced by low‐ and moderate‐income households.